1994
DOI: 10.1111/j.1476-5381.1994.tb17163.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible roles of protein kinases in neutrophil chemotactic factor production by leucocytes in allergic inflammation in rats

Abstract: 1 In an air pouch-type allergic inflammation model in rats, leucocytes that had infiltrated into the pouch fluid collected 4 h after the antigen challenge produced proteinaceous chemotactic factors for neutrophils when they were incubated in the medium. 2 To clarify the mechanism of activation of the infiltrated leucocytes in producing these factors, the effects of protein kinase inhibitors on neutrophil chemotactic factor production were examined. 3 When the infiltrated leucocytes were incubated for 4 h in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…These results indicate that the leukocytes from the immunized rats pro duce higher amounts of MIP-2 than the leukocytes from the nonimmunized rats. Recently we found that the leukocytes infiltrated into the pouch fluid of the immunized rats pro duce LDNCF-1 and LDNCF-2 much more actively than do the leukocytes from the nonimmunized rats through the mechanism of activation of tyrosine kinase and protein ki nase C but not cAMP-dependent protein kinase [16], Be cause LDNCF-2 has been identified as rat MIP-2 in this study, the mechanism of action of the protein kinase inhib itors on LDNCF-2 production by the leukocytes might be able to analyze in the gene expression level.…”
Section: Discussionmentioning
confidence: 95%
“…These results indicate that the leukocytes from the immunized rats pro duce higher amounts of MIP-2 than the leukocytes from the nonimmunized rats. Recently we found that the leukocytes infiltrated into the pouch fluid of the immunized rats pro duce LDNCF-1 and LDNCF-2 much more actively than do the leukocytes from the nonimmunized rats through the mechanism of activation of tyrosine kinase and protein ki nase C but not cAMP-dependent protein kinase [16], Be cause LDNCF-2 has been identified as rat MIP-2 in this study, the mechanism of action of the protein kinase inhib itors on LDNCF-2 production by the leukocytes might be able to analyze in the gene expression level.…”
Section: Discussionmentioning
confidence: 95%
“…However, the possibility cannot be presently excluded that the beneficial effects of cycloheximide observed here were mediated by mechanisms not related to direct inhibition of programmed cell death. Some alternative mechanisms might be enhancement of cellular glutathione levels because of reduced cysteine use (Ratan et al, 1994) or suppression of neutrophil chemotaxis (Tanabe et al, 1994). Yet another possible mechanism is raised by the interesting finding that low concentrations of cycloheximide that produce only limited inhibition of protein synthesis can induce the production of Bcl2 and antioxidant enzymes (Furukawa et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…4). Therefore, it is possible that the IgE-sensitized mast cells in the air pouch-type allergic inflammation model participate in the production of MIP-2 and contribute to neutrophil infiltration in this model [Tanabe et al, 1994[Tanabe et al, , 1995aXiao et al, 1997]. Furthermore, we suggested that p38 MAPK and p44/42 MAPK play important roles in mediating the antigen-induced MIP-2 mRNA stabilization, because the p38 MAPK inhibitor SB203580 and the MEK inhibitor PD98059 lowered the antigen-induced retardation of MIP-2 mRNA decay (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rat cytokine-induced neutrophil chemoattractants (CINCs) are the gro-gene products consisting of CINC-1, CINC-2a, CINC-2b, and CINC-3 [Nakagawa et al, 1994]. CINC-3 is also known as macrophage inflammatory protein-2 (MIP-2) and leucocyte-derived neutrophil chemotactic factor-2 (LDNCF-2) [Tanabe et al, 1994[Tanabe et al, , 1995c. In the rat air pouch-type allergic inflammation model, MIP-2 (CINC-3, LDNCF-2) plays an important role in neutrophil infiltration [Tanabe et al, 1994[Tanabe et al, , 1995aXiao et al, 1997].…”
mentioning
confidence: 99%
See 1 more Smart Citation